Using Technology Acceptance Model (TAM Model) to Increase Effectiveness the Use of Human Resource Information System (HRIS) : Empirical Studies at a Private Company in Indonesia - Sumantri, Hariyadi; Tukiran, Martinus; Hannan, Sufrin (Jurnal Manajemen, 2023)
Studies related to HRIS Applications show that the Technology Acceptance Model can be used to increase the use of HRIS Applications in a company. This research aims to test and reveal empirical factors that influence using the HRIS-Pakoku Application in the Pako Group. The two direct factors are perceived ease of use and perceived usefulness, and the indirect factor is a behavioural intention to use. This research was conducted at Pako Group using a questionnaire survey method, and samples were taken using the proposed stratified random sampling technique of 138 employees using HRIS at Pako Group. SEM analysis is used to determine the influence between research variables. The research results show a positive and significant influence of perceived ease of use on actual system use, a positive and significant influence of perceived usefulness on actual system use, and a positive and significant influence of behavioural intention to use on actual system use. There is a positive and insignificant influence of perceived ease of use on actual use through intention to use behaviour, and there is a positive and insignificant influence of perceived usefulness on actual system use through intention to use behaviour.